Carbon Nanotube Based Metal–Organic Framework Hybrids From Fundamentals Toward Applications. Issue 4 (11th December 2021) - Chronopoulos, Demetrios D.; Saini, Haneesh; Tantis, Iosif; Zbořil, Radek; Jayaramulu, Kolleboyina; Otyepka, Michal
Abstract: Metal–organic frameworks (MOFs) materials constructed by the coordination chemistry of metal ions and organic ligands are important members of the crystalline materials family. Owing to their exceptional properties, for example, high porosity, tunable pore size, and large surface area, MOFs have been applied in several fields such as gas or liquid adsorbents, sensors, batteries, and supercapacitors. However, poor conductivity and low stability hamper their potential applications in several attractive fields such as energy and gas storage. The integration of MOFs with carbon nanotubes (CNTs), a well‐established carbon allotrope that exhibits high conductivity and stability, has been proposed as an efficient strategy to overcome such limitations. By combining the advantages of MOFs and CNTs, a wide variety of composites can be prepared with properties superior to their parent materials. This review provides a comprehensive summary of the preparation of CNT@MOF composites and focuses on their recent applications in several important fields, such as water purification, gas storage and separation, sensing, electrocatalysis, and energy storage (supercapacitors and batteries). Future challenges and prospects for CNT@MOF composites are also discussed. Abstract : This review critically summarizes smart integration of metal–organic frameworks with carbon nanotubes (CNT@MOF) including its recent progress in synthesis, design, critical challenges in properties, and potential applications.